2021
DOI: 10.3389/fnana.2020.616465
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Feedback Neurons in the High-Level Visual Cortical Areas That Project Directly to the Primary Visual Cortex in the Cat

Abstract: Previous studies indicate that top-down influence plays a critical role in visual information processing and perceptual detection. However, the substrate that carries top-down influence remains poorly understood. Using a combined technique of retrograde neuronal tracing and immunofluorescent double labeling, we characterized the distribution and cell type of feedback neurons in cat’s high-level visual cortical areas that send direct connections to the primary visual cortex (V1: area 17). Our results showed: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 120 publications
(231 reference statements)
2
14
0
Order By: Relevance
“…In conclusion, our results suggest that suppression of top-down influence with c-tDCS in A7 decreases neuronal activity in the V1 cortex, which is consistent with some of previous studies using neural imaging measurement 6 , 12 and some single-unit recording studies that report facilitatory top-down effects on most neurons in the V1 or low-level visual cortex 7 , 9 , 33 , 41 , and is also supported by neuronal tracing studies that identify most feedback neurons as excitatory cells 43 , 44 although top-down modulation may mediated by a mechanism of disinhibition 41 . Our result is opposite to the results of other studies that report inhibitory top-down effects of V2/V3 cortex on V1 neurons in primate and mouse 8 , 29 , 32 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In conclusion, our results suggest that suppression of top-down influence with c-tDCS in A7 decreases neuronal activity in the V1 cortex, which is consistent with some of previous studies using neural imaging measurement 6 , 12 and some single-unit recording studies that report facilitatory top-down effects on most neurons in the V1 or low-level visual cortex 7 , 9 , 33 , 41 , and is also supported by neuronal tracing studies that identify most feedback neurons as excitatory cells 43 , 44 although top-down modulation may mediated by a mechanism of disinhibition 41 . Our result is opposite to the results of other studies that report inhibitory top-down effects of V2/V3 cortex on V1 neurons in primate and mouse 8 , 29 , 32 .…”
Section: Discussionsupporting
confidence: 90%
“…Some authors report top-down facilitation effect on the late-phase neuronal response 41 or late ERP components (90–140 ms) 38 , whereas others find a strong attentional modulation on the initial response of VEP component (57 ms) and population response during the first wave of visual processing (< 100 ms) in the human V1 cortex 39 , 40 . It is likely that the top-down effect on the initial and late response components in the V1 may depend on the strength of top-down influence during different tasks 39 or the source of top-down connections from different cortical areas to the V1 cortex 42 , 43 or types of visual signals such as figure-ground stimuli 41 . Considering that A7 has a weblike and direct projections to the V1 10 , 12 , and tDCS manipulation may trigger a large scale of top-down influence from A7, it could be reasonable that visual stimulation with full-screen size gratings may potentiate a drastic top-down effect on VEPs, even the initial VEP components, in the V1 as observed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that the normal top-down influence of A7 in the absence of c-tDCS enhances neuronal activity in V1, consistent with previous studies in neuroimaging ( Chen et al., 2014 ; Galuske et al., 2002 ; Huang et al., 2004 ; Liang et al., 2007 ; Tong et al., 2011 ; Yang et al., 2016b ) and single-unit recordings ( Huh et al., 2018 ; Jansen-Amorim et al., 2012 ; Wang et al., 2000 , 2007 , 2010 ; Zhang et al., 2014 ). Our results are also supported by neuronal tracing studies that showed that most feedback neurons are CaMKII-positive pyramidal neurons ( Budd, 1998 ; Han et al., 2008 ; Johnson and Burkhalter, 1994 , 1997 ; Pan et al., 2021b ) and may use primarily excitatory amino acid as neurotransmitters ( Johnson and Burkhalter, 1994 ; van Loon et al., 2015 ). The observed excitatory top-down influence of A7 on V1 is, however, different from reports of inhibitory top-down effects of V2/V3 on V1 neurons in primate and rodent studies ( Hishida et al., 2019 ; Maniglia et al., 2019 ; Nassi et al., 2013 , 2014 ).…”
Section: Discussionsupporting
confidence: 83%
“…The results suggest that top-down influence of A7 affects both early and later responses in V1, consistent with some previous studies ( Foster et al., 2021 ; Kelly and Mohr, 2018 ; Zhang et al., 2015 ), but inconsistent with other studies that report top-down effects only on the later responses in V1 ( Alilović et al., 2019 ; Baumgartner et al., 2018 ; Kirchberger et al., 2021 ). Future studies are necessary to clarify if top-down effects on the early and late response components in V1 depend on the strength of the top-down influence in different tasks ( Kelly and Mohr, 2018 ; Slotnick, 2018 ) or the source of top-down influence ( Johnson and Burkhalter, 1997 ; Pan et al., 2021b ). We found that behavioral contrast detection is more highly coupled to early sensory responses in V1, which is consistent with previous observations ( Bao et al., 2010 ; Richter et al., 2018 ; Zhang et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%